The reproductive biology of Pinguipes brasilianus Cuvier, 1829 (Osteichthyes: Pinguipedidae) in temperate rocky reefs of Argentina - Villanueva Gomila, Gabriela Lujan (2015)
Pinguipes brasilianus is a conspicuous and abundant rocky-reef fish inhabiting the Northern Patagonian gulfs of Argentina, Southwest Atlantic. This study describes its reproductive biology in this region. We made macroscopic and histological descriptions of the testis and ovary development, analyzed the evolution of the gonadosomatic index (GSI) in both sexes throughout the year, and estimated fecundity and length at 50% maturity for females. Pinguipes brasilianus is a multiple spawner with indeterminate annual fecundity and an extended reproductive season, encompassing austral spring and summer. Low GSI values in males (monthly means ranged between 0.11% and 0.75%) and low relative fecundity in female fish (between 2 and 44 oocytes/g) are consistent with a need of close proximity between male and female during oocyte fertilization, sexual courtship and with spawning in pairs and/or within reef crevices. The estimated length at 50% maturity (± SD) for females was 15.22 ± 0.43 cm total length. Although P. brasilianus shares the main reproductive features of its congeneric species Pinguipes chilensis, male GSI and female length at 50% maturity in P brasilianus were markedly lower than those reported for P. chilensis, while relative and batch fecundity were greater in fish of the same size.